Challenges for group leaders working with families dealing with early psychosis: a qualitative study. Issue 1 (December 2015) - Nilsen, Liv; Norheim, Irene; Frich, Jan; Friis, Svein; Røssberg, Jan
Abstract Background Family work is one of the best researched psychosocial interventions for patients with chronic psychosis. However, family work is less studied for patients with a first episode psychosis and the studies have revealed contradicting results. To our knowledge, no previous studies have examined qualitatively group leaders' experiences with family work. In the present study we wanted to explore challenges faced by mental health professionals working as group leaders for family interventions with first episode psychosis patients. Method A qualitative exploratory study was carried out based on digitally recorded in-depth interviews and a focus group interview with nine experienced mental health professionals. The interviews were transcribed in a slightly modified verbatim mode and analysed by systematic text condensation. Results Challenges faced by group leaders was classified into six categories: (1) Motivating patients to participate, encouraging potential participants was demanding and time-consuming; (2) Selecting participants by identifying those who can form a functional group and benefit from the intervention; (3) Choosing group format to determine whether a single or multi-family group is best for the participants; (4) Preserving patient independence, while also encouraging them to participate in the intervention; (5) Adherence to the protocol, while customizing adjustments as needed; (6) Fostering good problem-solving by creating a fertile learning environment and choosing the most appropriate problem to solve. Conclusions Group leaders face challenges related to recruitment and selection of participants for family work, as well as in conducting sessions. Awareness of these challenges could help health professionals more specifically to tailor the intervention to the specific needs of patients and their families.